Lymphatic endothelial cell RXRα is critical for 9‐cis‐retinoic acid‐mediated lymphangiogenesis and prevention of secondary lymphedema. Issue 1 (15th December 2022) - Sung, Cynthia; Jiao, Wan; Park, Sun Young; Cooper, Michael; Bouz, Antoun; Choi, Dahae; Jung, Eunson; Kim, Gene; Hong, Young Kwon; Wong, Alex K.
Abstract: Secondary lymphedema is a debilitating disease characterized by abnormal soft tissue swelling and caused by lymphatic system dysfunction. Despite a high prevalence of secondary lymphedema after cancer treatments, current management is supportive and there are no approved therapeutic agents that can thwart disease progression. We have previously demonstrated that 9‐cis‐retinoic acid (9‐ cis RA) has the potential to be repurposed for lymphedema as it mitigates disease by promoting lymphangiogenesis at the site of lymphatic injury. Although the efficacy of 9‐ cis RA has been demonstrated in previous studies, the mechanism of action is not completely understood. In this study, we demonstrate that when RXRα is specifically deleted in lymphatic endothelial cells, 9‐ cis RA fails to induce lymphangiogenesis in vitro and prevent pathologic progression of postsurgical lymphedema in vivo. These findings demonstrate that downstream nuclear receptor RXRα plays a critical role in the therapeutic efficacy of 9‐ cis RA in postsurgical lymphedema.